2016
DOI: 10.15835/nsb819766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foliar Application with Salicylic Acid on Biochemical Characters of Canola Plants under Cold Stress Condition

Abstract: In this study the effect of foliar application of salicylic acid on the chlorophyll content, antioxidant enzymes activity, and the content of solute protein and proline were investigated in two canola varieties (Brassica napus L., cv ‘RGS’ and ‘Licord’) leaves during 0, 24, and 48 hours after salicylic acid treatment. The results showed that the content of total chlorophyll was decreased in ‘RGS’ cultivar during the experiment and this process was related with increasing of salicylic acid concentration. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…The increase of SSC content could promote the viscosity, elasticity, and cell sap concentration of protoplasts, thereby improving the water absorption and water retention capacity of crops (Wang et al, 2016). Osmotic regulation contributes to cell development and promotes plant growth under drought stress (Keshavarz et al, 2016). In this study, after drought stress, the accumulation of SSC content in TY2 and DY2 was significantly increased.…”
Section: Responses Of Physiological Indicators To Drought Stress At the Seedling Stage In Oatmentioning
confidence: 52%
“…The increase of SSC content could promote the viscosity, elasticity, and cell sap concentration of protoplasts, thereby improving the water absorption and water retention capacity of crops (Wang et al, 2016). Osmotic regulation contributes to cell development and promotes plant growth under drought stress (Keshavarz et al, 2016). In this study, after drought stress, the accumulation of SSC content in TY2 and DY2 was significantly increased.…”
Section: Responses Of Physiological Indicators To Drought Stress At the Seedling Stage In Oatmentioning
confidence: 52%
“…The enzyme peroxidase is used to collect reactive oxygen species in order to prevent excessive damage to the active plasmid membrane. Superoxide dismutase enzyme regulates the concentration of hydrogen peroxide and superoxide in the cell and is an important factor in the plant's defense system against antioxidant stress . Hassanpour and Niknam stated that drought stress increased the activity of ascorbate peroxidase, superoxide dismutase, and peroxidase.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide dismutase enzyme regulates the concentration of hydrogen peroxide and superoxide in the cell and is an important factor in the plant's defense system against antioxidant stress. [38] Hassanpour and Niknam [8] stated that drought stress increased the activity of ascorbate peroxidase, superoxide dismutase, and peroxidase. Mallick et al [39] observed that proline increased in some wheat genotypes due to drought stress.…”
Section: Effect Of Drought Stress On Production Of Proline Catalasementioning
confidence: 99%
“…Plant hormones can play vital roles in plant growth and development processes response to various abiotic and biotic stress (Shaki et al 2019). Plant hormones have been used to improve the growth and development of different crop species (Keshavarz et al 2016;Dotto & Neumann Silva 2017;Shaki et al 2020). The Gibberellic acid (GA3) plays essential roles in seed germination, stem elongation, leaf expansion and reproductive development (Khan & Chaudhry 2006).…”
Section: Introductionmentioning
confidence: 99%